Pengaruh Waktu Tunggu Dan Respon Petugas Terhadap Kepuasan Pasien Di RSUD Dr. Alberth Torey Kabupaten Teluk Wondama - Nethanelia Pokko, Jenny; Ma’rufi; Chandra M, Freddy; Zamli (Jurnal Kesehatan Mahardika, 2024)
The quality of health services is closely related to patient satisfaction and is one measure of the success of the quality of health services. The purpose of the study was to determine the effect of patient waiting time and officer response on patient satisfaction at the Outpatient Unit of the Regional General Hospital (RSUD) Dr. Alberth H. Torey Teluk Wondama. The research method used quantitative research with a cross sectional study design. The population is outpatients at RSUD Dr. Alberth H. Torey Teluk Wondama totaling 480 people taken in March 2024. The sample size needed was 83 people. Data collection using questionnaires and interviews. Data analysis using the Chi-Square Test / Fisher's Exact Test. The results showed that there was a relationship between waiting time and patient satisfaction in the outpatient unit of Dr. Alberth H. Torey Hospital with a p value = 0.011 (p value <0.05), and there was a relationship between officer response and patient satisfaction in the outpatient unit of Dr. Alberth H. Torey Hospital with a p value = 0.002 (p value <0.05). There is a relationship between waiting time and officer response with patient satisfaction in the outpatient unit of Dr. Alberth H. Torey Teluk Wondama Hospital.